Treatment option in immature permanent teeth with acute apical abscess a case report - Hurint, Theresia PL.; Natsir, Nurhayaty; Dwiandhany, Wahyuni S.; Nugroho, Juni J.; Hikmah, Noor; Trilaksana, Aries C. (Hasanuddin University, 2023)
Objective: This case report aims to describe the treatment of open apex on maxillary incisors by performing an apical plug with MTA to induce the formation of a calcified barrier.Method: A 7-year-old female was referred with a fracture on upper right front tooth. Intraoral examination showed fracture on maxillary right central incisor with swollen gums in labial region. Periapical radiograph revealed a wide root canal with open apex and radiolucency. The diagnosis was pulpal necrosis with acute apical abscess.Results: Traumatized immature permanent teeth can cause pulpal necrosis, which can progress to an acute apical abscess. This condition will stop root development and open apex.Conclusion: Treatment of immature